Understanding the impact of the COVID-19 pandemic on the career choices of individuals by using career sailboat model - Nazir, Thseen; Özçiçek, Ayşe (Frontiers in Education, 2023)
Career Sailboat Model (CSM) is a postmodernist career-counseling model developed by Korkut-Owen et al. (2010). In CSM, career decision-making involves four interrelated and interactive dimensions: individual/personal factors, social factors, system-related factors, and chance factors. According to the CSM, because these factors are interrelated, in case of disclusion of any of them while making a career decision may lead an individual to make unfitting career choices. From this perspective, an unexpected event such as a natural disaster can be considered under the category of chance factor and it can impact other factors -individual, social and system-related- which have an influence on the individual’s career choice as well as its impact varies according to the individual, social and system-related factors. This article aims to understand the effects of COVID-19, as a chance factor, on other constructs -individual/personal, social, and system-related- of the CSM and their overall impacts on people’s career decision-making process. To be able to understand the impact of such a global calamity, the research done during the COVID-19 period has been used in this research. It is concluded that when a calamity like COVID-19 comes into the scene as a chance factor can have a significant impact on an individual's perspective regarding their career.